Comparison of irrigation performance assessment of D.I Cikahuripan according to irrigation network maintenance exploitation guidelines with fuzzy set theory - Hamka M. Noris; Putra Krisna; Fauzi Rizki; Saputri Utamy Sukmayu; Triono (BIO Web of Conferences)
Performance assessment of irrigation networks is an integral part of irrigation management. Irrigation managers conduct it and form the basis for policymaking in the irrigation area being evaluated. Performance assessment involves six aspects of irrigation networks, including physical infrastructure, crop productivity, operation and maintenance (O&M) support facilities, personnel organization, documentation, and Water User Farmer Association (P3A) organization. Currently, performance assessment, on some aspects, still relies on the experience of field officers or observers. This research aims to evaluate the performance of irrigation networks by applying fuzzy set theory to reduce subjectivity in accordance with the method used by the Balai, which refers to Permen PUPR No. 12/PRT/M/2015 concerning Guidelines for Exploitation and Maintenance of Irrigation Networks. Input data comes from the performance assessment of irrigation networks in the Cikahuripan Irrigation Area in 2023. The results showed that fuzzy analysis of the performance value of irrigation networks in the Cikahuripan Irrigation Area reached 70.17%, while the assessment carried out manually reached 67.57%. The comparison between the assessment using fuzzy set theory and manual methods shows a difference of 2.6%. This shows that the fuzzy set theory method can be used to evaluate the performance of irrigation systems.